Intravenous colistin use in children: Single-center experience [Çocuklarda intravenöz kolistin kullanımı: Tek merkez deneyimi] - (:unkn) unknown (AVES Ibrahim Kara, 2014)
Objective: Colistin, a bactericidal antibiotic, was used in the 1960s for the treatment of infections by gram-negative bacteria. Because of its side effects and the development of safer drugs, its use was abandoned in the 1980s. In infections within clinics where multi-drug-resistant gram-negative bacteria (MDRGNB) (especially Pseudomonas spp. and Acinetobacter spp.) are present, colistin usage is suggested if there is drug resistance to any other antibiotics. Nephrotoxicity is one of the commonly observed adverse effects following intravenous (IV) administration of colistin. Nephrotoxicity is dose-dependent and reversible. The aim of this study is to evaluate the efficacy and safety of colistin in MDRGNB infections occurring in pediatric and neonatal patients. Material and Methods: The files of all patients under the age of 18 who were given IV colistin treatment, apart from inhaler treatments, were retrospectively investigated. Demographic characteristics of patients, risk factors for systemic infection, causative microorganisms, and susceptibilities and side effects of colistin were evaluated. Results: Twenty-three patients meeting the criteria were included in the study. The median age was 2 years (4 days-17 years). Colistin was used for infections caused by MDR Acinetobacter baumannii 78.2% (18/23) and MDR Pseudomonas aeruginosa 21.8% (5/23). MDR A. baumannii was found growing in the blood cultures of 15 patients and in the urine, wound, and respiratory sample of 1 patient. MDR P. aeruginosa was found in respiratory samples of 4 patients and the blood culture of 1 patient. The duration of treatment with colistin was a median of 13 (4-30) days. All patients were given additional antibiotics with colistin. The most commonly used antibiotics were carbapenems (13 patients), with 5 patients given sulbactam-ampicillin, 4 given ciprofloxacin, and 3 given aminoglycoside. One patient died during treatment with colistin. No patient developed nephrotoxicity or neurotoxicity. Conclusion: It appears that IV colistin use is effective and safe for MDRGNB treatment in pediatric patients. © 2014 by Pediatric Infectious Diseases Society.
Keywords: Antibiotic resistance; Colistin; Gram-negative bacterial infections; Hospital infections